Elucidation of chemical profiles and molecular targets of Mondia whitei leave fractions bioactive as novel therapeutics: an in vitro and in silico assay - Hope Onohuean; Fanny Eseohe Onohuean; Sharon Iyobor Igbinoba; Joseph Obiezu Chukwujekwu Ezeonwumelu; Peter Chinedu Agu; Josiah Eseoghene Ifie; Tusubira Deusdedit; Patrick Maduabuchi Aja (Journal of Genetic Engineering and Biotechnology, 2022)
Abstract Background Mondia whitei root is often used in Africa as a local therapeutic agent for libido enhancement. The fractions of the M. whitei leaves (MWL) lack chemical characterization of their bioactive components and possible molecular targets. We characterized and investigated its molecular target as therapeutic agents in an in vitro and in silico assay. Mineral compositions, antioxidant, and GC-MS characterization were studied. The cytotoxicity effect was measured on HeLa and HT-29 cells by MTT assay. In silico potential inhibitors of Cathepsin B (CathB) as a cancer biomarker were determined. Results The flame photometry produced marked Na+ and K+. GC-MS revealed eighteen bioactive components. The fractions (chloroformic 47.00, ethanolic 45.52, and aqueous 40.13) of MWL caused a higher inhibition ratio compared to standards. The MWL showed a significant cytotoxic effect on the treated cell lines at concentrations of 150 and 200 μg/ml and 100, 150, and 200 μg/ml for HT-29 and HeLa cells, respectively. Ten bioactives (MWL 4, 5, 6, 8, 9, 10, 14, 15, 17, and 18) showed potential inhibition of CathB with binding affinities of −4.40 to −8.3 Kcal/Mol. However, MWL 4, 9, 14, and 17 which have higher binding affinities (−6.7, −7.1, −8.2, and −8.3, respectively) than the standard inhibitor (−6.5) were the lead molecules. Conclusion These chemical profiles and potential molecular targets unraveled in this study propose that MWL has a promising anticancer activity. Graphical Abstract